Bacteriological Profile of PUS / WOUND SWAB Andantimicrobial Susceptibility of Staphylococcus Aureus Isolated from of PUS & WOUND SWAB of Indoor Patients of Tertiary Care Hospital in Durg, Chhattisgarh India - Bankar, Nandkishor; Wankhade, Archana; Bramhane, R B; Hathiwala, Riddhi; Chandi, Dhruba Hari (International Journal of Innovative Research in Medical Science, 2018)
Wound infection can be caused by variety of organisms like bacteria, virus, fungi and protozoa and may co-exist as poly microbial communities. Even though the bacterial profile of pus samples in many studies remain the same, the antibiotic resistance pattern of these isolates has shown a lot of variations. This study was conducted in the department of microbiology of a private tertiary care hospital CCM Medical College Durg, Chhattisgarh over a period of one year from January 2017 to December 2017. Antibiotic sensitivity testing of Staphylococcal isolates was performed by modified Kirby Bauer’s disc diffusion method. Total of 387 samples were processed for aerobic culture and sensitivity, of which in 304 (78.55%) samples single growth was observed. Of the total 304 isolates, 274 isolates were from surgical units and 30 isolates from medicine units. Isolation of Gram positive and Gram negative organisms was 144 (47.36%) and 158 (51.97%) respectively and 2 (0.65%) species were candida. Antibiotic susceptibility testing was done on 104 Staphylococcus aureusisolates for MRSA detection and antibiotic resistance pattern. 93.3% isolates were resistant to penicillin followed by cotrimoxazole (67.3%) and erythromycin (50%). Resistance to Linezolid was observed in 2.9% cases while vancomycin and Teicoplanin showed 1.9 % and 6.7% resistance. 26.9 % isolates were MRSA. This study gives an outline of antibiotic susceptibility of Staphylococcal isolates to formulate the local antibiotic policy to start the appropriate empirical antibiotic treatment before the culture reports are available.